Dietary contribution of wild edible plants to women's diets in the buffer zone around the Lama forest, Benin - an underutilized potential - Boedecker, J.; Termote, Céline; Assogbadjo, A.E.; Damme, Patrick van; Lachat, Carl (Springer, 2014)
Rural populations in developing countries face food insecurity and malnutrition despite being surrounded by extraordinary biodiversity. The international community increasingly recognizes the role of agro-biodiversity and Wild Edible Plants (WEPs) in their contributions to managing risk and building resilience and sustainable food systems. Studies on real contributions of WEPs to peoples’ diets, however, are uncommon. This study assessed the contribution of WEPs to diets of women living in the buffer zone of the Lama forest in southern Benin. During the long dry season, a cross-sectional survey was carried out on 120 women, covering their knowledge and attitudes towards WEPs and two non-consecutive 24-h recalls of their WEP consumption. Contribution of WEPs to total dietary intake was low due to infrequent use and small portion sizes. The highest nutrient contributions of WEPs measured were for copper (13.9 %) and iron (4.6 %) but the majority of the women had intake values below the Estimated Average Requirements (EARs) for these elements - copper 65 % and iron 91 % Women’s dietary diversity was significantly higher among WEP consumers than non-consumers, mainly due to higher consumption of dark green leafy vegetables. WEPs were less consumed as a replacement for other foods but rather as a complement to the diet. The study population generally appreciated WEPs, while some constraints were reported regarding preparation, conservation and commercialization. Before widely promoting WEP consumption in order to exploit their dietary potential, additional investigations are needed into their nutrient composition, cultural and market value, their sustainable harvest levels and possible integration into innovative farming systems.